2021
DOI: 10.7759/cureus.17924
|View full text |Cite
|
Sign up to set email alerts
|

The Prediction of Malignancy Risk in Thyroid Nodules Classified as Bethesda System Category III (AUS/FLUS) and the Role of Ultrasound Finding for Prediction of Malignancy Risk

Abstract: To predict the risk of malignancy in category III of the Bethesda System for Reporting Thyroid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
3
5
0
Order By: Relevance
“…This contradicts the findings of a retrospective study involving AUS/FULS nodules, which found a significant association between nodule site (right vs. left vs. bilateral) and the final pathology (p < 0.001). 24 Moreover, our findings found no correlation between nodule size and final pathology; this concurred with previous studies. 20 , 25 …”
Section: Discussionsupporting
confidence: 92%
“…This contradicts the findings of a retrospective study involving AUS/FULS nodules, which found a significant association between nodule site (right vs. left vs. bilateral) and the final pathology (p < 0.001). 24 Moreover, our findings found no correlation between nodule size and final pathology; this concurred with previous studies. 20 , 25 …”
Section: Discussionsupporting
confidence: 92%
“…The authors reported that in the presence of any one of these suspicious features, ultrasound had a pooled sensitivity and specificity of 0.75 and 0.48, respectively, and with any two or three suspicious features, the sensitivity and specificity increased to 0.77 and 0.71, respectively. Alshahrani et al (20) noted that nodules with multiple numbers, irregular margins, microcalcification, and hypoechogenicity were significantly more likely to be malignant based on an analysis of 187 patients. A similar finding was also confirmed by Cho et al (21), Erdogan-Durmus et al (2), and in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Alshahrani et al. ( 20 ) noted that nodules with multiple numbers, irregular margins, microcalcification, and hypoechogenicity were significantly more likely to be malignant based on an analysis of 187 patients. A similar finding was also confirmed by Cho et al.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the majority of thyroid nodules assigned to this category qualify for diagnostic surgery to determine the final diagnosis [ 3 , 4 , 10 ]. Overall, there is considerable variability between cytopathologists as well as the institutions that use this category [ 11 , 12 ]. Based on Mosca et al’s [ 6 ] opinion, we also confirmed that the value of this cytology diagnosis obtained through ultrasound-guided fine-needle aspiration biopsy (UG-FNAB) procedures is strongly dependent on the examiner’s experience and other technical details.…”
Section: Introductionmentioning
confidence: 99%